5+1/3x-9=-2

Simple and best practice solution for 5+1/3x-9=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+1/3x-9=-2 equation:



5+1/3x-9=-2
We move all terms to the left:
5+1/3x-9-(-2)=0
Domain of the equation: 3x!=0
x!=0/3
x!=0
x∈R
We add all the numbers together, and all the variables
1/3x-2=0
We multiply all the terms by the denominator
-2*3x+1=0
Wy multiply elements
-6x+1=0
We move all terms containing x to the left, all other terms to the right
-6x=-1
x=-1/-6
x=1/6

See similar equations:

| t=-4t^2+16t+48 | | 2x-5(x-3)=9x-10) | | -5x+8=−5x+8=-4x+9−4x+9 | | 15-42x=143 | | 3x-3=9-1x | | 4y+2(y-7)=130 | | (x)/(-5)=-8 | | 59=x-8 | | X+(2y-9)=24 | | F(1/3)=8-3x | | -16=n+7 | | 17=-3x+5x+1 | | n-2(2n+3)=3 | | -7m-8=-10-7m | | |4x-4|=8x+3| | | N+2n+5=3n+5 | | -64=x+5 | | 15x+42=143 | | 11y-5+2y-5y+6=10 | | 3x+817= | | 4y=18. | | 20-2s+10=-20-7s | | 15+42x=143 | | 3x-x-6=9 | | x-1=84 | | 6)6+6n)-1=323 | | x²-4x+48=0 | | 451.80=190+1.19x | | 10-5t=5t-10 | | |k|=1 | | x/1=-6 | | -9x(X)3=-135 |

Equations solver categories